Kultur Sekolah Dalam Membangun Karakter Siswa di MTS Muhammadiyah 15 Medan - M Taufik Kamil; Ahmad Safii Marpaung; Musthopa Husein (Kitabah: Jurnal Pendidikan Sosial Humaniora, 2023)
The purpose of the research is to ensure and build student character to make good and disciplined personalities through school culture, this research method uses qualitative methods, data collection is based on the author's field research and interviews with teachers about the quality of student character. The results of the study, namely researchers found many activities in school culture that can build the character of students both from extracurricular activities, co-curricular activities, positive routine activities, and programmed activities